Central and peripheral changes in the retina and choroid in patients with diabetes mellitus without clinical diabetic retinopathy assessed by ultra-wide-field optical coherence tomography angiography - Zhao, Qing; Wang, Chuting; Meng, Lihui; Cheng, Shiyu; Gu, Xingwang; Chen, Youxin; Zhao, Xinyu (Frontiers in Public Health, 2023)
Background: To explore the central and peripheral retinal and choroidal changes in diabetic patients without clinical diabetic retinopathy (DM-NoDR) using ultra-wide-field swept-source optical coherence tomography angiography (UWF-SS-OCTA). Methods: Sixty-seven DM-NoDR eyes and 32 age-matched healthy eyes were recruited. Retinal and choroidal parameters, including qualitative retinal microangiopathy, vessel flow (VFD) and linear density (VLD), thickness, and volume, were measured in the central and peripheral areas of the 24×20 mm2 UWF-SS-OCTA images. Results: DM-NoDR eyes had significantly more nonperfusion area and capillary tortuosity than controls in the central and peripheral areas (P<0.05). The presence of central capillary tortuosity was associated with higher levels of serum creatinine (OR 1.049, 95%CI 1.001-1.098; P=0.044) and blood urea nitrogen (OR 1.775, 95%CI 1.051-2.998; P=0.032) in DM-NoDR eyes. For DM-NoDR eyes versus controls, VFD in the 300-µm annulus around the foveal avascular zone, superficial capillary plexus (SCP), and full retina, and SCP-VLD significantly decreased, while VFD in the deep capillary plexus (DCP), retinal thickness, and retinal volume increased (P<0.05). Analysis in the central and peripheral areas recapitulated all these findings, except for decreased peripheral thickness and volume and no difference in peripheral DCP-VFD. In DM-NoDR eyes, choriocapillaris-VFD, choroidal thickness, and choroidal volume increased in the central area, while VFD in the large and medium choroidal vessel layer decreased in the whole image (P<0.05). Conclusion: Retinal and choroidal changes already existed in the central and/or peripheral areas of DM-NoDR eyes. UWF-SS-OCTA, enabling the visualization of the peripheral fundus area, is a promising image technique for the early detection of fundus changes in DM-NoDR patients.